PERFORMANCE, VARIANCES AND HERITABILITY FOR SEVENTEEN GENOTYPES OF DURUM WHEAT (Triticum durum Desf.) - Ahmed A. Ahmed (Mesopotamia Journal of Agriculture)
Sixteen new durum wheat genotypes in addition to the local variety, Um-Rabeeh were studied in RCBD with three replications under the rainfed conditions of northern region of Iraq to study: number of days to 50% anthesis, plant height, spike length, number of grains/spike, number of spikes/m2 , biological yield, grain yield, harvest index, 1000-grain weight and protein percentage were studied. Phenotypic and genetic variances were highly significant for all the characters. Phenotypic correlation was positive and significant between number of days to 50 % anthesis and each of spike length and biological yield as well as between 1000- grain weight and protein percentage. Genetic correlation was positive and significant between harvest index and grain yield, number of spikes /m2 and protein percentage and between grain yield and biological yield. Broad–sense heritability estimates were high for number of days to 50% anthesis, plant height, biological yield, grain yield, harvest index, 1000- grain weight and protein percentage.